Parâmetros genéticos da concentração de ferro e de zinco em sementes de feijão andino - Zemolin, Allan Emanoel Mezzomo (2015)
The aim of this work was to investigate if occurs maternal effect for iron and zinc concentrations in Andean bean seeds, to obtain genetic parameters estimates for these minerals, and to select recombinants for the bean biofortification program. For this, crosses were performed between the parents IAC Boreal x Light Red Kidney, and Ouro Branco x Light Red Kidney, to produce F1, F1 reciprocal, F2, F2 reciprocal and backcrossed RC11 (F1 x P1) and RC12 (F1 x P2) generations. Parents and the other generations obtained were evaluated at a field experiment conducted at 2014 dry season, in Santa Maria, RS. In the bean seeds of the segregating populations obtained, the iron concentration range from 24.70 to 102.40 mg kg-1 of dry matter DM and the seed zinc concentration range from 10.70 to 37.50 mg kg-1 of DM, without that the expression of maternal effect was observed. The broad-sense heritability estimates for the seed iron concentration in the Andean beans range from 52.36 to 67.83%, and for zinc, the range was from 63.36 to 72.22%. The narrow-sense heritability estimates for seed iron concentration ranged from 19.04 to 45.29%, and, for zinc, from 31.04 to 63.60%. The selection gains for the seed iron and zinc concentrations ranged from 18.58 and 17.21%, respectively. Therefore, from the tested crosses, it is possible to obtain recombinants with high iron and zinc concentrations in Andean bean seeds.